Optimal Tilings of Bipartite Graphs Using Self-Assembling DNA - Redmon, Eric; Mena, Miles; Vesta, Megan; Renzyl Cortes, Alvi; Gernes, Lauren; Merheb, Simon; Soto, Nick; Stimpert, Chandler; Harsy, Amanda (The PUMP Journal of Undergraduate Research, 2023)
Motivated by the recent advancements in nanotechnology and the discovery of new laboratory techniques using the Watson-Crick complementary properties of DNA strands, formal graph theory has recently become useful in the study of self-assembling DNA complexes. Construction methods based on graph theory have resulted in significantly increased efficiency. We present the results of applying graph theoretical and linear algebra techniques for constructing crossed-prism graphs, crown graphs, book graphs, stacked book graphs, and helm graphs, along with kite, cricket, and moth graphs. In particular, we explore various design strategies for these graph families in two sets of laboratory constraints.